The Impact of natural resources on economic development in Africa - PORTUGAL, Kilton Jose Luis Lauter (KDI School, 2016)
This paper studied the association between economic development in Africa and natural resource wealth founded on panel data econometric techniques. With three different indicators that could proxy for resource dependence, the outcomes suggested that natural resources were important to predict economic growth in African countries. Some indicators have negative and other indicators have positive coefficients and are not statistically significant in all the models estimated. Overall, the results show that the natural resources were insignificant to predict economic development in Africa, at least over the sample period considered. The evidence is robust to alternative model specifications such as different sets of control variables and regression methods.
Thesis(Master) --KDI School:Master of Development Policy,2016